2015
DOI: 10.1002/adma.201503672
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Controlled Colloidal Superstructures: Long‐Range Plasmon Resonance Coupling in Particle Monolayers

Abstract: Particle interactions, from pronounced dipolar plasmon coupling to noncoupling in colloidal monolayers with interparticle distances of hundreds of nanometers, are demonstrated. Macroscopically sized, hexagonal monolayers with exceptionally high degrees of order are fabricated in one step. Time controls the interparticle spacing and no further processing is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 23 publications
2
87
1
Order By: Relevance
“…Extinction spectra (right) show the plasmon resonance of the metal cores and long‐range dipolar plasmon coupling for decreasing interparticle distances. Reproduced with permission …”
Section: Discussionmentioning
confidence: 99%
“…Extinction spectra (right) show the plasmon resonance of the metal cores and long‐range dipolar plasmon coupling for decreasing interparticle distances. Reproduced with permission …”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement to the results of our previous work, were we observed pronounced coupling for Ag@Au-PNIPAM particles, with Ag@Au cores of 100 nm in diameter, in periodic arrays only for inter-particles distances smaller than 450 nm. [13] The blue line in figure 2 M corresponds to a spectrum measured for the binary honeycomb lattice. This spectrum shows an intermediate absorbance as compared to the two individual monolayers (red and black line).…”
Section: Monolayer Fabrication By Interface-mediated Self-assemblymentioning
confidence: 99%
“…[17] We have previously shown that this deformation depends on the time that the particles rest at the air/water interface. [13] Consequently, time might be used to fabricate particle arrays with various lattice spacings. Figure 2 C shows a TEM image recorded from a monolayer that was prepared by the sequential deposition of a first Au@Au-PNIPAM monolayer and a second Ag@Au-PNIPAM monolayer on the same TEM grid.…”
Section: Monolayer Fabrication By Interface-mediated Self-assemblymentioning
confidence: 99%
See 2 more Smart Citations